2015
DOI: 10.1007/s11325-015-1145-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for automobile accidents caused by falling asleep while driving in obstructive sleep apnea syndrome

Abstract: PurposeWe examined the risk factors for automobile accidents caused by falling asleep while driving in subjects with obstructive sleep apnea syndrome (OSAS).MethodsWe asked licensed drivers with history of snoring and excessive daytime sleepiness who had undergone polysomnography (PSG) at the Department of Sleep Medicine/Sleep Disorders Center at Aichi Medical University Hospital to complete the questionnaires on accidents caused by falling asleep while driving. As a subjective measure of sleepiness, we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…IL-6 = interleukin-6, PVT = Psychomotor Vigilance Task significantly with automobile and other accidents. [41][42][43][44] Thus, ESS and PVT are inexpensive and easy-to-use protocols that may be useful in routine practice for predicting risks associated with impaired performance and attention, such as traffic accidents., However, MSLT is a useful, albeit expensive and time-consuming, tool to measure physiological sleep propensity, and may be a good predictor of cardiometabolic risk, as assessed by inflammation, in patients with OSA. 7,45 There are several strengths and limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 = interleukin-6, PVT = Psychomotor Vigilance Task significantly with automobile and other accidents. [41][42][43][44] Thus, ESS and PVT are inexpensive and easy-to-use protocols that may be useful in routine practice for predicting risks associated with impaired performance and attention, such as traffic accidents., However, MSLT is a useful, albeit expensive and time-consuming, tool to measure physiological sleep propensity, and may be a good predictor of cardiometabolic risk, as assessed by inflammation, in patients with OSA. 7,45 There are several strengths and limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Drowsy driving by people with OSA can lead to motor vehicle accidents, which result in economic and health burdens. 6,7 National Center for Statistics and Analysis data reveal that of 6 million motor vehicle accidents (5-year average, 2005-2009), 1.4% involve drowsy driving and 2.5% of fatal crashes involve drowsy driving. 8 Among noncommercial drivers, untreated OSA increases the risk of motor vehicle accidents 3-to 13-fold.…”
Section: ■ Drowsy Drivingmentioning
confidence: 99%
“…Accordingly, driving simulator research shows that the performance impairment in drivers suffering from OSAS is comparable to the impairment as a consequence of illegal alcohol consumption or sleep deprivation [12]. While reports differ, the majority of evidence supports the principle that driving risk in OSAS is more closely related to the degree of daytime sleepiness than the objective severity of sleep-disordered breathing as measured by AHI [4,[13][14][15]. The importance of sleepiness as the major contributing factor to MVA risk in OSAS is supported by the recent report of KARIMI et al [16] who demonstrated that excessive sleepiness based on an Epworth sleepiness score (ESS) >15 significantly related to MVA rate, whereas AHI did not.…”
Section: Role Of Sleepiness In Osas and Increased Driving Riskmentioning
confidence: 99%